1990
DOI: 10.1007/bf00403319
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin 2 receptor antibody attenuates low-dose streptozotocin-induced diabetes in mice

Abstract: Summary. Recent evidence indicates that activated T cells and macrophages play an important role in the induction of insulitis and diabetes in certain strains of mice treated with multiple subdiabetogenic doses of streptozotoein. In the present study, we treated C57BL/6J mice with five daily doses of 40 mg/ml streptozotocin and examined the prophylactic effect of an anti-interleukin 2 receptor monoclonal antibody (PC61). In mice treated with streptozotocin, interleukin 2 receptor-positive mononuclear cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
4
5
0
Order By: Relevance
“…Both of these findings suggest that there are important pathogenic differences between SZ-induced DM and the NOD mouse model of type 1 DM, since TNF-plays an age-dependent dichotomic role in the latter [15]. That anti-IL-2R mAb were incapable of counteracting the diabetogenic effects of SZ agrees with some but not all previously published findings [9,12]. Thus, Hatamori et al [12] showed a preventive effect of anti-IL-2R mAb prophylaxis in SZ-induced DM.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both of these findings suggest that there are important pathogenic differences between SZ-induced DM and the NOD mouse model of type 1 DM, since TNF-plays an age-dependent dichotomic role in the latter [15]. That anti-IL-2R mAb were incapable of counteracting the diabetogenic effects of SZ agrees with some but not all previously published findings [9,12]. Thus, Hatamori et al [12] showed a preventive effect of anti-IL-2R mAb prophylaxis in SZ-induced DM.…”
Section: Discussionsupporting
confidence: 86%
“…That anti-IL-2R mAb were incapable of counteracting the diabetogenic effects of SZ agrees with some but not all previously published findings [9,12]. Thus, Hatamori et al [12] showed a preventive effect of anti-IL-2R mAb prophylaxis in SZ-induced DM. Hence unlike in the NOD mouse [15] endogenous IL-2 is not required for the diabetogenic effects of SZ to occur in mice.…”
Section: Discussionsupporting
confidence: 77%
“…In conclusion, the accumulated evidence suggests that MD-STZ induces severe pancreatic b cell injury which, at least on a NOD background, is further exacerbated by ab T cell-mediated damage. The recovery from hyperglycaemia exhibited by 4/12 TCR-a ¹/mice, in contrast with the high sensitivity of NOD-scid/ scid mice to MD-STZ, indicates, as suggested previously [7], that the DNA repair defect in scid/scid mice may be an important additional determinant in susceptibility to IDDM induced by MD-STZ, and in the absence of ab T cells IDDM is less severe, or transitory.…”
Section: Discussionsupporting
confidence: 56%
“…The recovery from hyperglycaemia exhibited by 4/12 TCR-a ¹/-mice, in contrast with the high sensitivity of NOD-scid/ scid mice to MD-STZ, indicates, as suggested previously [7], that the DNA repair defect in scid/scid mice may be an important additional determinant in susceptibility to IDDM induced by MD-STZ, and in the absence of ab T cells IDDM is less severe, or transitory. …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation